The continuing evolution of auditing science: Megatrends and research opportunities for the 1990s* - TOMASSINI, LAWRENCE A. (Contemporary Accounting Research, 1990)
During the past 15 years, the field of auditing has evolved as a scientific discipline. This paper discusses the continuing evolution of auditing science by identifying current megatrends in the auditing environment. These megatrends include (1) the expanding scope of attestation and related audit services, (2) new competition and mergers between accounting firms, (3) changing information technology, and (4) an emerging global market for audits. Research opportunities for the 1990s that relate to such trends are illustrated to stimulate additional progress in the field. Finally, implications for interdisciplinary research and education and training future auditors are discussed. Résumé. Depuis 15 ans, le domaine de la vérification a gagné le rang de discipline scientifique. L'auteur traite de l'évolution incessante de la science de la vérification et détermine les mégatendances actuelles dans le secteur. On retrouve parmi ces mégatendances 1) l'élargissement de la portée de l'attestation et des services de vérification connexes, 2) la concurrence inédite que se livrent les cabinets comptables et les fusions dont ils font l'objet, 3) l'évolution de la technologie de l'information et 4) un marché global en émergence pour les services de vérification. L'auteur décrit les avenues de recherche qu'offrent ces tendances pour les années 1990, en vue de stimuler les progrès dans le domaine. Enfin, il traite des conséquences en matière de recherche interdisciplinaire et de formation théorique et pratique des futurs vérificateurs.